Building stories - Ware, Chris (Pantheon Books, a division of Random House, Inc., 2012)
Presents an illustrated tale, told in various books and folded sheets, about the residents in a three-story Chicago apartment building, including a lonely single woman, a couple who are growing to despise each other, and an elderly landlady